2011
DOI: 10.5539/jas.v4n3p281
|View full text |Cite
|
Sign up to set email alerts
|

Response of Growing Rabbits to Diets Containing Different Levels of Protein and Radish (Raphanus sativus L) Seeds

Abstract: This work aimed to study the effect of two different levels of ration protein supplemented with Radish (Raphanus sativus L) seeds (RS). Rabbits were classified into four equal groups (G1-G4). The1 st and 3 rd groups received basal ration with 100 % and 90 % of protein requirement level and served as first and second control respectively. The 2 nd and the 4 th groups received basal ration with 100 and 90% of protein supplemented with RS at the level 1.5%, respectively. The 90% of protein level significantly (P<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Evaluating Table 2, it is clear that the dietary plant extracts, Lippia citriodora, Solanum lycopersicum and Raphanus sativus, produced no effects on productive parameters. Even Abedo et al (2012), supplementing growing-rabbits feed with 1.5% of radish seeds, observed no effects on body weight, daily weight gain and on slaughter performance, compared with the control group.…”
Section: In Vita and Post Mortem Measurementsmentioning
confidence: 83%
“…Evaluating Table 2, it is clear that the dietary plant extracts, Lippia citriodora, Solanum lycopersicum and Raphanus sativus, produced no effects on productive parameters. Even Abedo et al (2012), supplementing growing-rabbits feed with 1.5% of radish seeds, observed no effects on body weight, daily weight gain and on slaughter performance, compared with the control group.…”
Section: In Vita and Post Mortem Measurementsmentioning
confidence: 83%
“…According to [27], the amount of black seed extract in broiler diet feed that was inoculated at 1.5%, 3.0%, and 4.5% decreased linearly as the dose of black seed extract increased. Moreover, [32] found that adding Radish seeds at 1.5% level to rabbit's diets showed insignificantly (p>0.05) increased the feed intake and feed conversion ratio compared to the control diet. Concerning the Radish seed oil as feed additive for quail or poultry there is scarcity of researches to compare our results with them.…”
Section: Feed Intake (Fi) and Feed Conversion Ratio (Fcr)mentioning
confidence: 94%
“…This stimulates or promotes the effective utilization of feed nutrients which may result in better BW and BWG [31]. However supplementing RS at 1.5% level to rabbit diets led to insignificant increase of the final BW and BWG compared to the control [32]. Additionally, the presence of biologically active components like fat-soluble factors and stimulants for the digestive system may have contributed to the enhancement of BW by supplementing the diet with black seed extract, which may be essential for growth.…”
Section: Body Weight (Bw) and Body Weight Gain (Bwg)mentioning
confidence: 99%